PENGARUH CURRENT RATIO, RETURN ON ASSETS DAN EARNING PER SHARE TERHADAP HARGA SAHAM - Erfandi Yuliawan; Achmad Zainuri; Umi Nadhiroh; Nurul Hidayah (Commodities, Journal of Economic and Business, 2023)
The stock price reflects the value of a company. If the company achieves good performance, then the company's shares will be in great demand by investors. This study aims to examine the effect of CR, ROA and EPS on stock prices. The population of this research is the food and beverage subsector industrial company listed on the Stock Exchange for the period 2013-2017. The research sample was taken by purposive sampling method. Secondary data obtained from the IDX Investment Gallery at UNISKA Kediri. Data collection techniques using the documentation method. Data analysis techniques with multiple linear regression, test the coefficient of determination and hypothesis testing. The results showed that partially the ROA and EPS variables had a positive and significant effect on stock prices, while the CR variable had a negative and not significant effect on stock prices. The ROA variable has the most dominant influence. Simultaneously the CR, ROA and EPS variables have a positive and significant effect on stock prices. Adjusted R-square value of 0.688, which means the ability of independent variables to explain variations in the dependent variable is 68.8% while the remaining 31.2% is influenced by other factors outside of this study. These results can be used to guide investors before investing in the capital market.